A real-world study based on the FAERS database evaluating adverse drug reactions in three amphotericin B lipid formulations - Binliang Tong; Jiaqi Wang; Yanjing Zhang; Yan Liu; Jing Wang; Liguang Duan; Yuhang Yan; Qixuan Sun; Yueyao Luan; Jing Yu; Chunhua Zhou (Journal of Pharmaceutical Policy and Practice)
Background: Amphotericin B (AmB) remains the cornerstone in the treatment of severe fungal infections. However, selecting an appropriate lipid-based formulation for different clinical scenarios remains a challenge for clinicians and clinical pharmacists.Methods: Adverse event (AE) reports from the FDA Adverse Event Reporting System (FAERS) database (Q1 2004–Q3 2024) were retrospectively analysed to assess the safety profiles of three lipid formulations of AmB: liposomal amphotericin B (L-AmB), amphotericin B lipid complex (ABLC), and amphotericin B colloidal dispersion (ABCD). The baseline patient characteristics, AE distributions, and prognostic outcomes of severe AEs were examined. SPSS software was used to compare AE occurrences among the three groups.Results: A total of 3284 patient reports were included, comprising 3108 in the L-AmB group, 142 in the ABLC group, and 34 in the ABCD group. Within 30 days, AEs were reported in 666 cases (L-AmB), 72 cases (ABLC), and 13 cases (ABCD) (P < 0.001). AEs were categorised using the System Organ Class (SOC) and Standardized MedDRA Querie (SMQ). Compared with the L-AmB group, the ABLC group had a significantly higher incidence of hypersensitivity and hypertension; whereas hypokalemia was significantly lower (P < 0.001). Compared to the L-AmB and ABLC groups, the ABCD group had a significantly higher incidence of haematopoietic thrombocytopenia (P < 0.001). Prognostic analysis indicated that the incidence of life-threatening events was significantly higher in the ABCD group than in the L-AmB and ABLC groups (P < 0.001).Conclusion: The safety profiles of L-AmB, ABLC, and ABCD differ among organ systems. These findings highlight the need for individualised treatment strategies based on drug-specific safety characteristics and patient-specific clinical conditions to ensure optimal drug selection and patient safety.